Canadian 24-hour movement guidelines for the early years (0-4 years): exploring the perceptions of stakeholders and end users regarding their acceptability, barriers to uptake, and dissemination - Negin Riazi; Subha Ramanathan; Meghan O'Neill; Mark S. Tremblay; Guy Faulkner (BMC, 2017)
Abstract Background It is important to engage stakeholders and end users in the development of guidelines for knowledge translation purposes. The aim of this study was to examine stakeholders' (experts in pediatric and family medicine, physical activity knowledge translation, and research) and end users' (parents and early childhood educators) perceptions of the Canadian 24-Hour Movement Guidelines for the Early Years (0-4 years). Methods Stakeholders (n = 10) engaged in telephone interviews and end users (n = 92) participated in focus groups (n = 14) to discuss perceived clarity and need for the guidelines, potential barriers to implementation, identification of credible messengers, and methods for dissemination of the guidelines. A thematic analysis was conducted. Results The proposed guidelines were very well received by both stakeholders and end users. A clear need for such guidelines was identified, and most believed the guidelines were achievable. Stakeholders and end users identified several potential barriers to uptake, including low awareness of current guidelines; 'daily challenges' such as allure of screen time, lack of time, and competing priorities; and challenges in the context of shifting social norms. A range of methods and messengers of dissemination were identified. Medical and child care settings were the most frequently cited places for dissemination, and physicians and early childhood educators were the most common suggestions for messengers. Conclusions There was consistent support for the Canadian 24-Hour Movement Guidelines for the Early Years (0-4 years) from both stakeholders and end users. Moving forward, it is important to dedicate appropriate support and funding toward dissemination efforts in order to reach end users, particularly parents and early childhood educators.